Analysis of online impedance measurement range based on voltage disturbance injection. (December 2020) - Li, Fei; Wu, Jintao; Huang, Yao; Zhang, Yongxin; Zhang, Xing; Ma, Mingyao
Abstract: The harmonic injection method is often used to measure the impedance of grid-connected inverter, which is necessary for impedance-based stability analysis of grid-connected systems. This paper proposes an online impedance measurement range analysis method that takes into account the grid impedance, electrical signal measurement range, and the upper limit of safety response of the equipment under disturbance in online measurement. This method provides a basis for the verification of impedance measurement results. It also can guide the design of the amplitude of the injected disturbance. The method helps to provide more accurate impedance measurement results, which is important for impedance-based stability analysis. Finally, this paper verifies the proposed impedance measurement range through simulation.